Strain and damage sensing behaviour of core reinforced braided composite rods - Rana, S. (2012)
In the present research, we have investigated the possibility of using core reinforced braided composite rods (BCRs) for self monitoring of deformation and damage. The BCRs were produced by braiding polyester fibres around a resin (unsaturated polyester) impregnated core, composed of glass and carbon fibre mixture, using a simple, single-step and low cost braiding process. The sensing behaviour was characterized by monitoring the change in electrical resistance with deformation using two terminal dc method. According to the experimental results, the composition with less amount of carbon fibre in the core showed the best strain sensing behaviour.